1987
DOI: 10.1007/bf02470598
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of peptic ulcer in the gastric tube used for esophageal replacement in adults

Abstract: Reported in this paper are two cases of peptic ulcer which developed in the gastric tube used for esophageal replacement following esophagectomy for esophageal tumors in adults. The results of our cases suggest that acid secretion from the mucosa of the gastric tube, in spite of truncal vagotomy and the state of the tube, seems to play important roles in the pathogenesis of peptic ulcer of the gastric tube after esophageal replacement, even though circulatory disturbances, due to postoperative irradiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 6 publications
0
24
1
3
Order By: Relevance
“…6) This condition reportedly allows bacterial proliferation and leads to enhancement of mucosal injury. 7,8) By contrast, the present case appeared to show conditions of both ischemic ulcer and enhanced gastric acid secretion, and the gastric tube ulcer was resistant to oral administration of both omeprazole and lansoprazole. We, therefore, performed H. pylori eradication therapy, since this bacterium plays an important role in the pathogenesis of gastric ulcer.…”
Section: Discussioncontrasting
confidence: 69%
“…6) This condition reportedly allows bacterial proliferation and leads to enhancement of mucosal injury. 7,8) By contrast, the present case appeared to show conditions of both ischemic ulcer and enhanced gastric acid secretion, and the gastric tube ulcer was resistant to oral administration of both omeprazole and lansoprazole. We, therefore, performed H. pylori eradication therapy, since this bacterium plays an important role in the pathogenesis of gastric ulcer.…”
Section: Discussioncontrasting
confidence: 69%
“…Uchida reported an incidence rate of 2.6% [2]. A prospective follow-up study using endoscopy in patients who underwent gastric tube reconstruction after esophageal cancer surgery indicated that 7 out of 114 patients (6.1%) had gastric ulcers [4].…”
Section: Discussionmentioning
confidence: 99%
“…The development of peptic ulcers in the gastric tube used for esophageal replacement in patients with esophageal cancer was previously considered a rare complication [1,2]. However, an increasing number of gastric tube ulcers have been reported recently [3].…”
Section: Introductionmentioning
confidence: 99%
“…51 Indeed, most of the reported cases of gastric tube ulcers did not involve pain, [7][8][9][10][11][12][13][14][15][16][17][18][51][52][53][54] so that ulcers of the gastric tube may be less frequently painful than ordinary gastric ulcers. However, the mechanism of ulcer pain remains controversial.…”
Section: Reasons For the Absence Of Pain In Gastric Tube Ulcersmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] The characteristics of the cases of perforated gastric tube after esophagectomy for esophageal cancer are presented in Table 1. Cases #6 12 and #11 15 had been taking an H2-blocker and nonsteroidal anti-infl ammatory drugs (NSAIDs), respectively, before the gastric tube was perforated, and the latter patient had a history of gastric ulcers.…”
Section: Case Reports On Perforated Gastric Tubesmentioning
confidence: 99%